Dismantling Monarchy: The Swedish Experience. - Erik Söderman (Royal Studies Journal)
Sweden’s dismantling of its semi-constitutional monarchy as a form of government was protracted and messy but not overly violent. The process started c.1718 and ended c.1974. Monarchy was not abolished, however, but sidelined. Its political-cum-administrative function was effectively folded into parliamentary democracy; its symbolic properties, its “true nature,” proved harder to manage. Among monarchists there were two lines of thought on the subject: emphasizing tradition or emphasizing modernity. The solution of choice was to “repurpose” it as protection for the two novelties of the nineteenth century—the nation state and democracy. With the King as a common symbol for the population, monarchy would be protection for the nation state and thereby also protection for democracy, because democracy can only exist within the framework of the nation state. The political-cum-administrative dismantling of monarchy took place 1848-1918, but the cultural wrangle about monarchy’s “true nature” took longer to resolve. Expanding on existing scholarship, this study demonstrates how Swedish monarchy, keeping some traditional veneer, has under the reign of Carl XVI Gustaf been reinterpreted from feudal remain to national symbol and a central part of modern democracy. Being this malleable, I would venture that monarchy has no inherent properties, political or otherwise, but rather adapts to circumstances.